ANALISIS KERUSAKAN DAUN BALING- BALING DAN METODE PERAWATAN YANG TEPAT - Dita Nurul Azizah (2022)
Ship propulsion has non-mechanical and mechanical systems, in non-mechanical systems you can use oars by relying on human power and relying on wind power, namely by sails. In this modern era, ships use more mechanical systems, namely by relying on the power generated by the main engine and transmitted to the blades of the propeller. The blade of the propeller is the part of the ship that is always submerged in the water so that it is susceptible to damage such as bends, fractures, or cavities so that special maintenance is needed to carry out repairs. This study was conducted to determine the contour pressure and cavitation fraction of the TB. ASP 26 propeller with the help of Numeca Fine Marine software, the first order fatigue cycle value of the ship TB. ASP 26 for 25 years, as well as maintenance methods on TB. ASP 26 ship propellers. which had a fracture. In this study, the finite element method was used.